(untitled) - Iriskulov , B.U.; Tursunkhojaeva , L.T. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
Carry out comparative analysis of attention, memory and mental potential of 2nd and 3rd year students of the medical academy. The "Cognitive Function Examination Card " was applied. The evaluation of cognitive functions was carried using 4 tasks aimed at assessing visual and auditory memory, voluntary attention and the level of generalization, one of the operations of thinking. Most students have better developed visual memory than auditory. Only 10.6% of students have a high ability to generalize. 45.2% of students have a low level of generalization.